Virtuous Innovations and the Circular Economy: A Chronicle of quantifying Sustainability-Oriented innovations in the Circular Economy - Alowais, Abdelaziz Abdalla (Journal of Ecohumanism, 2024)
The proposed paper explores the quantifying techniques scholars use globally to measure Sustainability-oriented Innovations in the circular economy. This conceptual paper highlighted the techniques and proposed formulas to measure the impact of innovation on the Circular Economy. The methods used to collect data are desk study and archival research. This paper collects past literature to explore as many quantifying techniques as possible in circular methods. Subsequently, previous literature suggests a hypothesis that can be explored further in a quantitative research design, and it is developed to study the link between sustainability-oriented innovations and the Circular economy. Furthermore, the paper’s purpose is not constrained to identify the relations only. It proposes methods of calculations that could be utilized to present factual results that can be benchmarked. This paper is an exploratory study that explores deep in the literature to grasp quantifying techniques that scholars with superior practical implications standardize. The quantifying techniques are either found or interpreted from the literature through the units of measurement in formulas.